PENERAPAN BIBLIOTERAPI UNTUK MENURUNKAN TINGKAT KECEMASAN ANAK USIA SEKOLAH SELAMA HOSPITALISASI DI RSUD DR. ADHIYATMA, MPH SEMARANG: APPLICATION OF BIBLIOTHERAPY TO DECREASE THE ANXIETY LEVEL OF SCHOOL-AGED CHILDREN DURING HOSPITALIZATION IN RSUD. DR. ADHIYATMA, MPH SEMARANG - Tri Santoso; Erni Suprapti (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
Hospitalization is a process that has planning or emergency reasons that require the child to stay in the hospital. Hospitalization at school-aged children is 6-12 years forcing children to part with their beloved environment such as family and group soisalnya causing anxiety. Anxiety is an emotional response to the assessment of something dangerous, associated with feelings of uncertainty, helplessness, fear of fear is not clear why. This case study illustrates the application of bibliotherapy to decrease the anxiety level of school-aged children during hospitalization. The case study design used is descriptive case study. The case study was conducted in RSUD Dr. Adhiyatma, MPH Semarang. result of case study got decrease of subject anxiety level I before application of bibliotherapy value of anxiety level 40 after application of bibliotherapy decrease to 34 and subject II anxiety level level before applying of bibliotherapy value of anxiety level 31 after application of bibliotherapy decrease to 26. subject of subject anxiety level decrease 6 value and subject II down 5 values.